PENGGUNAAN TEKNOLOGI AUGMENTED REALITY SEBAGAI ALAT UNTUK MEMPROMOSIKAN PARIWISATA BERKELANJUTAN - Siregar, Victor Marudut Mulia; Damanik, Erikson; Manalu, Andi Setiadi; Siringo-ringo, Eko Deswin; Parapat, Eka Pratiwi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop interactive tourism promotion media using Augmented Reality (AR) technology to increase the attractiveness of Sipolha Tourism Village as a leading destination in the Lake Toba area. Sipolha Village has great tourism potential but is not widely known compared to the surrounding areas. The research method used is design and development research which includes the design, development, implementation, and evaluation of an application called PAR Sipolha. This application presents 3D visualizations of local tourist attractions in an immersive manner and allows tourists to obtain information interactively. The prototype was developed using Blender for 3D object creation and Unity 3D with Vuforia Engine for AR integration. Implementation and testing were carried out with local communities and tourists to evaluate the effectiveness of the application. The results of the study show that the PAR Sipolha application is able to improve the tourism experience, provide interesting information, and support the promotion of sustainable tourism in Sipolha Village. This application is expected to be a model for the development of technology-based tourism in other tourist villages.